DEVELOPMENT OF METHODOLOGICAL TRAINING OF FUTURE FOREIGN LANGUAGE TEACHERS (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract: This article provides full information about the important stage of the research work and its importance and analysis of developing the skills of working with educational materials and developing the most effective educational technology for this pedagogical process in the development of methodological preparation of future foreign language teachers.